Customers perception towards ethical advertisements in Malaysia - Niha, Aishath (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
The fact that potentially unethical advertisements are reaching the marketplace suggests that current methods of evaluating advertisements may be insufficient for some of today‟s controversial or innovative advertising strategies. Interestingly, customers are constantly prone to advertisements both directly and indirectly. However, the question arises whether these advertisements are perceived to be ethical in the customers‟ mind. Many research experts believe such uncertainty could be an indication of a downfall for the advertising industry. It is worthwhile to be aware of the ethical issues facing advertisers in order to reduce the negative perceptions toward advertisements. This research focuses on some major perceptions for customers in addressing the perception towards ethical advertising. By examining whether the perceived factors such as deceptive messages, religiosity and emotional appeal can shape overall positive ethical perception. This research would provide marketers with a clear understanding on the ethical grounds. Therefore, if the accountable people such as advertisers and businesses work cooperatively and think about the consequences, these problems will be diminished in the future. Data was collected from 200 Malaysian customers and Structural Equation Modeling (SEM) was used to test the research hypothesis. The results confirmed that the independent variables used in this research do contribute to the customers perception on ethical advertisements on a large scale. Several propositions for future research have also been identified.